Volatile metabolomics and transcriptomics analyses provide insights into the mechanism of volatile changes during fruit development of ‘Ehime 38’ (Citrus reticulata) and its bud mutant - He, Jiaxian; Qin, Zeyu; Liu, Kexin; Li, Xiangyi; Kou, Yiming; Jin, Zhenghua; He, Ruiyuan; Hong, Min; Xiong, Bo; Liao, Ling; Sun, Guochao; He, Siya; et al. (Frontiers in Plant Science, 2024)
Volatile compounds are important determinants affecting fruit flavor. Previous study has identified a bud mutant of 'Ehime 38' (Citrus reticulata) with different volatile profile. However, the volatile changes between WT and MT during fruit development and underlying mechanism remain elusive. In this study, a total of 35 volatile compounds were identified in the pulps of WT and MT at five developmental stages. Both varieties accumulated similar and the highest levels of volatiles at stage S1, and showed a downward trend as the fruit develops. However, the total volatile contents in the pulps of MT were 1.4-2.5 folds higher than those in WT at stages S2-S5, which was mainly due to the increase in the content of d-limonene. Transcriptomic and RT-qPCR analysis revealed that most genes in MEP pathway were positively correlated with the volatile contents, of which DXS1 might mainly contribute to the elevated volatiles accumulation in MT by increasing the flux into the MEP pathway. Moreover, temporal expression analysis indicated that these MEP pathway genes functioned at different developmental stages. This study provided comprehensive volatile metabolomics and